2021
DOI: 10.1111/echo.15072
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of echocardiographic parameters in prone and supine positions in normal adults using a novel approach

Abstract: Background: Transthoracic echocardiography (TTE) in prone position is challenging.Innovative use of transesophageal echocardiography (TEE) probe to perform TTE for such patients has been described; but reproducibility and correlation of the TTE measurements by this technique with those obtained by the standard supine TTE study are still unknown. Methods:We enrolled 30 non-COVID-19 individuals, with a mean (SD) age 35 (10.9) years and 11 females, to study the agreement between the transthoracic measurements of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…In those circumstances, a TEE assessment is recommended given the improvement in quality image [ 10 ]. Nevertheless, its implementation has inherent difficulties that were accentuated by the COVID-19 pandemic: the probe is not available in many of the ICUs, a TEE trained physician is needed, has higher risk of aerosol generation, and require high workload including proper equipment sterilization and longer exposure to the patient’s infected particles [ 9 , 11 , 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…In those circumstances, a TEE assessment is recommended given the improvement in quality image [ 10 ]. Nevertheless, its implementation has inherent difficulties that were accentuated by the COVID-19 pandemic: the probe is not available in many of the ICUs, a TEE trained physician is needed, has higher risk of aerosol generation, and require high workload including proper equipment sterilization and longer exposure to the patient’s infected particles [ 9 , 11 , 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…A novel approach was proposed by Marvaki et al [ 14 ] and Taha et al [ 17 ]; in fact, they used a TEE probe to obtain traditional TTE windows in prone position. Taha et al found that all the measurements of the LVEDD, LVESD, SWT, PWT, and AoR dimensions in the prone position were accurate and replicated the corresponding measurements in the supine position well.…”
Section: Literature Reviewmentioning
confidence: 99%